The procedure of patients with infections candida guillermondii in Naval Hospital Dr. Ramelan Surabaya - Novitasari, Novitasari; Radithia, Desiana; Nafi’ah, Nafi’ah (Journal of Case Reports in Dental Medicine, 2020)
Objective: To find an adequate and efficient treatment for candidiasis patients with iron deficiency anemia. Methods: A 57year-old male patient came with several complains including the tip of the tongue feels thin but feels thick in the middle since ± a year ago and he feels its getting thicker and sore. Patients have smoking habit one pack of cigarettes per day since college (± 39 years ago). Patients doesnt have a diabetic disease but claim to suffer from cholesterol and high uric acid. The patient consumed turmeric and kenikir leafs to overcome his complains, but the symptoms did not decrease, ± a month ago, patient checked his complain to the dentist and given a medicine (Nystatin drop) but the complains had not subsided. Results This patient also has iron deficiency anemia. This condition can lead to candidiasis which causes disruption of oral ecology or changes in oral microbiology caused by iron deficiency. Conclusion: Candidiasis guillermondii in the oral cavity can be cured by anti-fungal treatment, KIE in patients, by instructing to improve oral hygiene and increase nutrient intake to speed up healing of candida infection